Male‐sterile maize plants produced by targeted mutagenesis of the cytochrome P450‐like gene (MS26) using a re‐designed I–CreI homing endonuclease. (5th November 2013) - Djukanovic, Vesna; Smith, Jeff; Lowe, Keith; Yang, Meizhu; Gao, Huirong; Jones, Spencer; Nicholson, Michael G.; West, Ande; Lape, Janel; Bidney, Dennis; Carl Falco, Saverio; Jantz, Derek; et al.
Summary The I–CreI homing endonuclease from Chlamydomonas reinhardti has been used as a molecular tool for creating DNA double‐strand breaks and enhancing DNA recombination reactions in maize cells. The DNA‐binding properties of this protein were re‐designed to recognize a 22 bp target sequence in the 5th exon of MS26, a maize fertility gene. Three versions of a single‐chain endonuclease, called Ems26, Ems26+ and Ems26++, cleaved their intended DNA site within the context of a reporter assay in a mammalian cell line. When the Ems26++ version was delivered to maize Black Mexican Sweet cells by Agrobacterium‐mediated transformation, the cleavage resulted in mutations at a co‐delivered extra‐chromosomal ms26‐site in up to 8.9% of the recovered clones. Delivery of the same version of Ems26 to immature embryos resulted in mutations at the predicted genomic ms26‐site in 5.8% of transgenic T0 plants. This targeted mutagenesis procedure yielded small deletions and insertions at the Ems26 target site consistent with products of double‐strand break repair generated by non‐homologous end joining. One of 21 mutagenized T0 plants carried two mutated alleles of the MS26 gene. As expected, the bi‐allelic mutant T0 plant and the T1 progeny homozygous for the ms26 mutant alleles were male‐sterile. This paper described the second maize chromosomal locus (liguless‐1 being the first one) mutagenized by a re‐designed I–CreI–based endonuclease, demonstrating the general utility of these molecules for targeted mutagenesis in plants.